Karakteristik dan Komposisi Minyak Atsiri dari Sampel Gabungan Daun-Ranting Limau Kuit Asal Astambul dan Aranio - Fitria, Delfa Nayla; Irwan, Azidi; Abdullah, Abdullah (Jurnal Natural Scientiae, 2024)
Limau kuit is believed to be a local orange from South Kalimantan. Limau kuit has a distinctive aroma different from other oranges and is thought from its essential oil. The essential oil from limau kuit has the potential to be extracted and produced into valuable goods. Limau kuit essential oil from a combination of leaves and twigs has never been reported before. The composition of essential oils is influenced by genetic and environmental factors. The region producing limau kuit in Kabupaten Banjar is in Kecamatan Astambul and Kecamatan Aranio. These places geographically have different conditions, especially the altitude of the location, so it is thought to have a difference in the essential oils. This research aims to obtain essential oil from the leaves and twigs of limau kuit by hydrosteam distillation and determine the characteristics and composition of each plant's origin. Hydrosteam distillation was carried out for 6 hours at 60-70 °C. The essential oil of leaves and twigs of limau kuit is transparent pale yellow and has an aroma similar to the source with an average yield of 0.6027% (v/w) or 0.5062% (w/w). The specific gravity, refractive index, optical rotation, and solubility in alcohol, respectively, of Astambul essential oil are 0.8540; 1.4792; (-14.05); and 1:6; and Aranio 0.8495; 1.4792; (+)0.16, and 1:7. Based on the results of GC-MS analysis, the components of Astambul and Aranio essential oils overall tend to be the same with a difference of 25%. Number of compounds in essential oil from Astambul was 32, while from Aranio was 38. The three main compounds in essential oils from Astambul and Aranio are g-terpinene, o-cymene, and (+)-bicyclogermacrene, with the respective %area in Astambul essential oil, was 25%; 13.22%, and 6.38%; and Aranio was 22.43%; 11.68%; and 5.88%.KEYWORD : Limau kuit leaves-twigs; essential oil; hydrosteam distillation; Astambul; Aranio.